The Transcription Factor Nrf2 - Antonio Morales-Gonzalez, Jose; Morales-Gonzalez, Angel; Osiris Madrigal-Santillan, Eduardo (IntechOpen, 2016)
Due to that at present, the majority of diseases are associated with alterations in oxidative stress and inflammatory processes, and in that Nrf-2 is a modulator of these processes; knowing how this transcriptional factor functions and is regulated opens a therapeutic window to diverse diseases. Therefore, the efforts of various investigation groups are centered on finding activators and/or inhibitors of Nrf-2 to prevent or control diverse diseases, for example, cancer, where it would be important to regulate Nrf-2 in order for it to activate apoptosis pathways in cancerogenous cells, or in neurodegenerative diseases where cell death is predominant, it would be important for Nrf-2 to activate antiapoptotic pathways.